Kajian Etnobotani Tanaman Pepaya (Carica papaya L.) di Díli, Timor-Leste - Pinto, Alice (Fakultas Biologi Universitas Gadjah Mada, 2024)
Abstract: Papaya is one of the traditional medicinal plant. All parts of this plant can be used as traditional medicine. This research aims to examine the ethnobotanical use of papaya plant by the people of Díli, Timor-Leste. The sample for this study was 50 people. It was carried out using a questionnaire, which contained structured questions. The result of this study showed that people obtain papaya from their home garden and use it freshly to make traditional medicine. The parts of papaya that can be used are: leaves, roots, fruit and flowers. These parts can be prepared using methods, such as: decoction, mixed with food, fried, consumed directly, heated in a fire, crushed and salad. These can be consumed by eating and drinking to treat internal diseases such as infections and parasites and others diseases of various body systems. It can be used by topical method and for bathing, to treat external diseases such as wounds. The quantity of consuming papaya can be once/day to three times/day. The time period needed to recover from diseases are varies from a day to recovery. This knowledge is obtained from the community itself, which needs to be preserved for future generations.